Analisis Kualitas Pelayanan Pengguna KIS Pada Pusat Kesehatan Masyarakan (Puskesmas) Di Beberapa Kabupaten Bogor - Putri Nurlailia Agustina; Sonny Fransisco Siboro; Syalum Fajrin; Anatassya Sagita Oktaviola (Universitas 45 Surabaya, 2024)
Quality of service is a focus on meeting customer expectations. Customer satisfaction is the primary goal of quality service. BPJS Health is a body that moves in the field of social security of Health. The aim of this study is to analyze the quality of BPJS health services in the puskesmas. Quality of service is physical proof, reliability, responsiveness, assurance and certainty, and empathy. This research is a descriptive method and a quantitative method. Data collection is carried out by dissemination of questionnaires to respondents, websites from various related sources. Sampling method is purposive sampling. Research results show that physical evidence, reliability, responsiveness, assurance and certainty, and empathy have a good percentage. However, this research suggests that the quality of service should be further improved by not distinguishing patients with BPJS or cash, implementing services according to health standards, improving hygiene at the practice, comfort especially for the elderly, providing information in detail and clearly, enhancing cooperation with hospitals so that more medical personnel, a friendly and polite attitude to be observed. Factors contributing to the low quality of services include lack of human resources and facilities, as well as lack of coordination between primary and higher levels of health care. This research provides important insights for improving the quality of health services in Puskesmas, especially for users of KIS in Bogor District.